An Investigation into the Impact of a Structured Teaching Program on the Knowledge of Women’s Rights in India Among Working Women in Selected Government Organizations in North Gujarat - Chetan Prakash Bardwal; Urvashi Solanki; Manisha Patel; Krishna Goswami; Maitri Chavda; Tanjila Mansuri; Meet Patel; Mitesh Parmar; Sakina Malpara; Aayushi Suthar; Apexa Prajapati; Nensi Khatri; et al. (International Journal of Community Health Nursing And Practices, 2025)
A study was conducted to evaluate the impact of a structured teaching program on the knowledge of women’s rights in India among working women in the government sector of North Gujarat. The research used an evaluative approach, specifically a pre-experimental design with a one-group pre- test and post-test. A non-probability purposive sampling method was used to select participants from a government sector in North Gujarat. The sample included 50 women who fulfilled the inclusion criteria established by the researcher. A structured questionnaire was created to evaluate the participants’ awareness of women’s rights. The data was analyzed using a paired t-test to determine the effectiveness of the teaching program. In the pre-test, the average knowledge score showed that 66% of the participants had poor knowledge (scoring 0–7) about women’s rights in India. Meanwhile, 24% of participants had an average knowledge score (8–14), and 10% had a good knowledge score (15–21). After the teaching program, there was a significant improvement in the participants’ knowledge, with the majority (86%) exhibiting good knowledge, and 14% showing average knowledge in the post-test. The calculated ‘t’ value (17.66) was greater than the table value (t = 2.1004) at a 0.001 level of significance. The hypothesis corresponding p-value was 0.001 which is small (less than 0.05), the null hypothesis is rejected. This suggests that the women’s understanding of their rights notably increased following the health education program.
Keywords: Assess; Effect; Knowledge; rights of women; structured teaching; women